Profile Teleradiography: A Diagnostic Means and a Prosthetic Construction Aid for the Removable Prosthesis - Sana Bekri; Mohammed Bechir Annebi; Hiba Triki (Dentistry, 2017)
The profile teleradiography finds its indication in removable denture each time that the complexity of the case requires it. It is used as a working tool with a clinical value for refining our diagnosis. The aim of this work is to establish, through a clinical case, the importance of this radiography in the diagnosis and prosthetic decision-making.